Peran Mediasi Akuntan Pajak Muda dalam Implementasi Coretax: Studi Fenomenologis tentang Kesadaran dan Kepatuhan Pajak di Kalangan Pemuda Indonesia - Ester Claudi Jayapriatna; Gatot Soeprianto (JURNAL ILMIAH GEMA PERENCANA, 2025)
This study examines the experiences of young people interacting with the Coretax system, which is positioned not merely as an administrative instrument but also as a medium for transforming the role of young professionals. They appear not only as implementers of fiscal policy but also as educational agents, drivers of social influence, and architects of trust within their peer communities. Using a qualitative approach based on in-depth interviews, this study found that Coretax is appreciated for its ability to simplify reporting mechanisms, provide real-time data access, and strengthen fiscal transparency. However, technical limitations such as system errors, an interface design that is less user-friendly for beginners, and a tax literacy deficit remain significant obstacles. The results of this study emphasize the strategic position of young accountants as epistemic mediators who bridge regulatory complexity with the educational needs of the digital generation. The implications of these findings indicate that the successful implementation of Coretax rests not only on technical improvements but also on the continuous orchestration of tax literacy, in order to foster inclusive, adaptive, and sustainability-oriented fiscal compliance in the digital era.